Enhancing Listening Comprehension Skills of EFL Learners Through Using Web-based Learning - Al-Shaimaa M. Al-Rashidy; Amany A. Alsabbagh (International Journal of Advanced Humanities Research)
The present study aimed at enhancing listening comprehension of EFL students through a Web-based listening program. For this purpose, one experimental group (N=37) was purposefully selected. They received a Web-based program on a Web site prepared by the researchers. The program included fifty lessons and two revisions. To test the program's effectiveness, pre and post tests of listening comprehension were prepared. The results were statistically analyzed by using the t-test to compare the mean scores of the pre-post tests. Results revealed the effectiveness of the Web-based program in developing EFL students' listening comprehension skills. Accordingly, discussion and interpretation of these results were provided as well as relevant recommendations and suggestions for further research.